Synthesis and Characterization of Layered Double Hydroxides as Materials for Electrocatalytic Applications - Domenica Tonelli; Isacco Gualandi; Elisa Musella; Erika Scavetta (Nanomaterials, 2021)
Layered double hydroxides (LDHs) are anionic clays which have found applications in a wide range of fields, including electrochemistry. In such a case, to display good performances they should possess electrical conductivity which can be ensured by the presence of metals able to give reversible redox reactions in a proper potential window. The metal centers can act as redox mediators to catalyze reactions for which the required overpotential is too high, and this is a key aspect for the development of processes and devices where the control of charge transfer reactions plays an important role. In order to act as redox mediator, a material can be present in solution or supported on a conductive support. The most commonly used methods to synthesize LDHs, referring both to bulk synthesis and in situ growth methods, which allow for the direct modification of conductive supports, are here summarized. In addition, the most widely used techniques to characterize the LDHs structure and morphology are also reported, since their electrochemical performance is strictly related to these features. Finally, some electrocatalytic applications of LDHs, when synthesized as nanomaterials, are discussed considering those related to sensing, oxygen evolution reaction, and other energy issues.